Nivel de vulnerabilidad de las cooperativas de ahorro y crédito por la aplicación de procedimientos de control, para mitigar el lavado de activos del sector el mercado mayorista, DMQ. - Sofía Elizabeth, Caiza Zapata (2017)
This academic article aims to analyze the vulnerability of the Savings and Credit Cooperatives by the application of control procedures, to mitigate money laundering, have analyzed 3 COAC that are within the sector the wholesale market, through the use of surveys conducted to 6 officials of the entities, as well as 14 of the clients to which we could determine that compliance is performed under the regulations imposed by the Superintendency of Popular and Solidarity Economy, however do not have automatic detections in lists of internal control and the infrastructure is not adequate, which has limited the number of clients and the increase in investments.